Assessment of phenol compound removal from olive oil mill wastewater by using peroxidases extracted from radish and nettle leaves - Bouslimi, Houda; Jouili, Hager; Caçador, Isabel; Sleimi, Noomene (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2019)
AbstractThe aim of this work is to evaluate the degree of degradation phenolic compounds in olive mill wastewater (OMW), using crude plant peroxidases. In fact, OMW was treated with crude peroxidases extracted from radish (Raphanus sativus L.) and nettle (Urtica urens L.) leaves. A significant reduction of more than 60% of total phenols was observed in OMW incubated with peroxidase crude extract during seven days. The present chromatographic data obtained by high performance liquid chromatography (HPLC) show that enzymatic treatment may change the composition of the polyphenols contained in the OMW. Thus, we observed a significant decrease in some phenolic acid levels, such as gallic acid, p-coumaric acid and hydroxytyrosol, and the disappearance of vanillic acid, compared to the non-treated OMW. Finally, phytotoxicity of the treated and non-treated OMW was tested by means of young sunflower plants (Helianthus annuus) grown in hydroponic medium. Our results showed that sunflower plants grow normally when the nutrient medium contains treated OMW; whereas they fade rapidly in the presence of non-treated OMW. We conclude that treatment of OMW with radish and nettle crude extracts could attenuate OMW phytotoxicity considerably.